Open water swimmer safety - Gerrard, D. (FINA World Sports Medicine Congress, 18, 2016)
Prof. David Gerrard, University of Otago (NZL) and Dr Kevin Boyd, (GBR) talk about "Open Water Swimmer Safety: Coaches` Role" at the FINA World Sports Medicine Congress 2016 ().